2000
DOI: 10.1164/ajrccm.162.1.9908105
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Tyrosine Kinase Signaling Cascade Attenuated Antigen Challenge of Guinea-Pig Airways In Vitro

Abstract: Activation of nontransmembrane protein tyrosine kinases (PTKs), phosphatidylinositol 3-kinase (PI3K), and mitogen-activated protein kinase (MAPK) has been shown to be responsible for high-affinity Fc receptor (Fcepsilon RI)-mediated mast cell degranulation. Effects of inhibitors of the PTK signaling cascade on ovalbumin (OA)-induced anaphylactic contraction of isolated guinea-pig bronchi and release of histamine and peptidoleukotrienes from chopped lung preparations were studied. Genistein (30 microM) and tyrp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Walker et al [14] described the crystal structure of PI3Kg with LY294002, showing that the morpholino group of LY294002 is absolutely required for binding and selectivity. Our present findings confirm our previous in vitro anti-inflammatory data [15,16] that inhibition of PI3K by LY294002 could attenuate OVA-induced pulmonary inflammation, release of Th2 cytokines into the airway, airway mucus production, and AHR in sensitized mice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Walker et al [14] described the crystal structure of PI3Kg with LY294002, showing that the morpholino group of LY294002 is absolutely required for binding and selectivity. Our present findings confirm our previous in vitro anti-inflammatory data [15,16] that inhibition of PI3K by LY294002 could attenuate OVA-induced pulmonary inflammation, release of Th2 cytokines into the airway, airway mucus production, and AHR in sensitized mice.…”
Section: Discussionsupporting
confidence: 92%
“…Our laboratory has recently demonstrated that LY294002, a PI3K inhibitor [13,14], significantly inhibited antigen-induced anaphylactic contraction of bronchial rings and release of histamine and peptidoleukotrienes from chopped lung preparations from sensitized guinea pigs [15], and thrombin-induced airway smooth muscle cell proliferation [16]. The purpose of the present study was to extend our recent in vitro findings of anti-inflammatory effects of LY294002 to an in vivo mouse asthma model.…”
Section: Introductionmentioning
confidence: 78%
“…Recently it has also been reported that they can markedly attenuate antigen-induced acute bronchoconstriction and airway hyperresponsiveness to inhaled methacholine in a guinea pig model of asthma [89]. Similar observations of Syk-selective inhibition have been published [75,89]. Piceatannol, a Syk-selective inhibitor, significantly diminished antigen-induced bronchial smooth muscle contraction and release of histamine and leukotrienes from lung fragments isolated from sensitized guinea pigs [75].…”
Section: The Blockade Of MC Activation: a New Approach To Mc−related mentioning
confidence: 54%
“…Genistein inhibits PTK activity through competitive inhibition at the ATP-binding domain of the kinase, whereas tyrphostin acts by competitive inhibition at the substrate site of the kinase [2]. Recently it has also been reported that they can markedly attenuate antigen-induced acute bronchoconstriction and airway hyperresponsiveness to inhaled methacholine in a guinea pig model of asthma [89]. Similar observations of Syk-selective inhibition have been published [75,89].…”
Section: The Blockade Of MC Activation: a New Approach To Mc−related mentioning
confidence: 79%
See 1 more Smart Citation